Exploring Maghrebi Literature Through the Lens of Active Learning Strategies - Florina Matu (Studies in 20th & 21st Century Literature, 2026)
The objective of this article is to share with its readers active learning strategies for the study of contemporary Maghrebi literature. The corpus comprises Maïssa Bey’s epistolary novel Nulle autre voix (2018) and two volumes of Leïla Slimani’s trilogy Le Pays des autres: La guerre, la guerre, la guerre (2020) and Regardez-nous danser (2022). I articulate the pedagogical value of three evidence-based practices that level the playfield for all learners: active-learning assessment tools designed in partnership with the students, embedding a growth- mindset approach to discuss content, and continuously soliciting students’ anonymous inputs throughout the semester by the means of anonymous questionnaires and polls.Thematically, students explore socio-political and cultural effects of Colonialism and Post-Colonialism and analyze how women characters articulate or express the problems of identity and resistance, gender roles and family dynamics, sexuality and difference, marriage, and womanhood. From a pedagogical perspective, this article incorporates specific examples of respectful classroom engagement, scaffolded reading guides aiming at increasing language proficiency, highly structured activities based on graphic organizers and note-takers, and collaborative learning.
Keywords: pedagogy; active learning; Maghreb; Maïssa Bey; Leïla Slimani; collaboration; students as partners